MODERN TRENDS AND DIRECTIONS OF PROFESSIONAL EDUCATION DEVELOPMENT - Kibrio Ergashevna Buriyeva (European Science Publishing, 2024)
The article describes the relevance of the use of modern pedagogical technologies in the field of vocational education, because the technologies that need to be used in their activities should be aimed at the formation and development of a personality that meets the needs of society and contribute to ensuring a decent level and continuous improvement of the quality of education. Such technologies allow us to move to a qualitatively new level of education. Traditional learning is a type of learning that ensures the reproductive assimilation of knowledge. The teacher informs the topic of the lesson, the goals, which in no way contributes to the emergence of cognitive interest among students. Today, the teacher ceases to be together with the student the bearer of the "objective knowledge" that he is trying to convey to him. Its main task becomes to motivate students to show initiative and independence in discovering new knowledge, to find ways to apply this knowledge in solving various problematic tasks. At the stage of finding a solution, the teacher encourages students to put forward and test hypotheses, i.e. ensures the "discovery" of knowledge through trial and error.
Keywords: pedagogical technologies, professional education, modern trends.